A coupling study of scavenging effect on pollutant formation and unclean combustion of a linear vibration engine - Liu Chunzhi; Zicheng Yuan; Jiangchuan Lu; Chenheng Yuan (Case Studies in Thermal Engineering)
Linear vibration engines, due to their flexible compression expansion characteristics and the coupling mechanism of vibration, combustion, and gas exchange, are expected to become the research focus of new clean energy conversion devices. This paper develops a systematical dynamic-thermodynamic model that mutually transfers the interaction parameters between combustion model, pollution model and the insight the of a linear diesel engine, and an iterative calculation schedule is proposed to solute the systematical model for the simulation of scavenging pressure effect on combustion and pollution. The results indicate that when the scavenging pressures are considered from 1.1 bar to 1.7 bar in 0.1 bar interval, there is an optimum scavenging pressure of 1.3 bar for fast combustion, more heat release, high thermal efficiency, because it provides fast reciprocating, large compression ratio, high in-cylinder gas pressure and temperature, bringing CO concentration of 0.12 % and NO mass fraction of 0.032 %. Decreasing the scavenging pressure leads to slow compression and more residual exhaust gas for incomplete combustion, and the max HC and soot concentrations are 0.080 % and 2.5e-8 respectively. Enhancing the pressure gives low compression ratio for combustion and reduces NO concentration to 0.019 % and soot concentration to 1.1e-8.